Monitoring Social and Economic Impacts of COVID-19 on Refugees in Uganda : Results from the High-Frequency Phone Survey, First Round (October-November 2020) - World Bank (World Bank, Washington, DC, 2021)
The High-Frequency Phone Survey for refugees in Uganda (URHFPS) tracks the socioeconomic impacts of COVID-19 on refugees. The World Bank (WB) in collaboration with the Uganda Bureau of Statistics (UBOS) and United Nations High Commissioner for Refugees (UNCHR) launched and conducted the URHFPS. The URHFPS tracks the impacts of the pandemic on a monthly basis for a period of three months. Data collection for the first round of URHFPS took place between October 22 – November 25, 2020. This brief discusses results from the first round of the URHFPS. Where possible and appropriate, results for refugees are compared to nationals by using the national High-Frequency Phone Survey on COVID-19 (HFPS). The survey sample includes respondents with active phone numbers that were selected randomly from the Profile Global Registration System (ProGres) of UNHCR, and the refugee household survey carried out by UBOS and the World Bank in 2018. The targeted sample includes 2,100 households and is representative at seven strata constructed as a combination of regions and different countries of origin: Kampala-Somalia, Kampala-other (Burundi, DRC, South Sudan), South West-Burundi (SW-Burundi), South West-DRC (SW-DRC), South West-South Sudan (SW-South Sudan), South West-Somalia (SW-Somalia), and West Nile-South Sudan (WN-South Sudan). In terms of population size, the largest strata are South West-DRC and West Nile-South Sudan. Both strata account for more than 85 percent of refugees in Uganda in 2020. The realized sample after the first round was 2,010 households. In order to reduce the bias related to only interviewing households with phone numbers and non-response, the data from the 2018 representative refugee household survey was used to produce and calibrate the weights for the phone survey.